Effects of Spreading Sequences on the Performance of MC-CDMA System with Nonlinear Models of HPA - Drotar, Peter; Gazda, Juraj; Kocur, Dusan; Galajda, Pavol (Společnost pro radioelektronické inženýrství, 2009)
Performance evaluation and comparison of multi-carrier code division multiple access (MC-CDMA) system model for different spreading sequences at the presence of Saleh and Rapp model of high power amplifier (HPA) is investigated. Nonlinear amplification introduces degradation of bit error performance and destroys the orthogonality among subcarriers. In order to avoid performance degradation without requiring extremely large backoffs in the transmitter amplifier, it becomes convenient to use nonlinear multi-user detection techniques at the receiver side. In order to illustrate this fact, microstatistic multi-user receiver (MSF-MUD) and conventional minimum mean square error receiver (MMSE-MUD) are considered and mutually compared. The results of our analyses based on computer simulations will show very clearly, that the application of nonlinear MSF-MUD in combination with Golay codes can provide significantly better results than the other tested spreading codes and receivers. Besides this fact, a failure of Walsh codes especially at the Saleh model of HPA will be outlined by using constellation diagram.
Keywords: MC-CDMA; HPA; Saleh model; Rapp model; PAPR; multi-user receivers